Student, teacher, and caregiver perceptions on implementing mental health interventions in Ugandan schools - Catherine Carlson (SAGE Publishing, 2021)
Background The vast majority of children and adolescents in low and middle-income countries (LMICs) lack access to interventions for mental health problems. Schools provide a critical platform for evidence-based intervention delivery for young people. However, a significant need exists to understand the implementation context and strategies for delivering school mental health interventions in LMICs. Methods We conducted a focused ethnography to explore students’, teachers’, and caregivers’ perspectives on implementing evidence-based mental health interventions (EBIs) within a widespread violence prevention program in Uganda. Data collection occurred in Kampala, Uganda, using two schools that have previously implemented an evidence-based violence prevention program widely used in Ugandan schools schools, the Good School Toolkit (GST). Trained, local researchers facilitated four focus group discussions (FGDs) with caregivers ( n  = 22), four FGDs with teachers ( n  = 25), and in-depth interviews with primary school students ( n  = 12). Verbatim transcripts were analyzed using a framework analysis approach. Results Participants revealed a school culture that promotes schools’ responsibility to students beyond academics, including positive teacher–student relationships. Participants recommended an implementation process that trains teachers and students in screening and referral, peer group delivery, and is accompanied by a school-wide approach to stigma reduction and mental health literacy. Participants fundamentally agreed that teachers could be trained as intervention facilitators. Conclusions This study highlights the potential advantage of leveraging an existing intervention that already addresses implementation factors, such as school culture, as a fertile platform for implementing interventions for child and adolescent mental health in LMICs. Plain language abstract Despite the growth of implementation research for child and adolescent mental health, the study of implementation science for child and adolescent mental health in low and middle-income countries (LMICs) remains scarce. Schools provide a critical platform for evidence-based intervention delivery for young people. However, a significant need exists to understand the implementation context and strategies for delivering school mental health interventions in LMICs. This study provides rich qualitative data describing the context and influences for the successful implementation of mental health interventions in LMIC schools. We conducted interviews and focus groups with teachers, students, and caregivers to determine their perspectives on implementing evidence-based mental health interventions (EBIs) within a widespread violence prevention program in Uganda. Participants revealed a school culture promoted by the existing program that promotes schools’ responsibility to students beyond academics, including positive teacher–student relationships. Findings suggest the existing program provides fertile ground for the successful implementation of evidence-based mental health interventions in schools.